WHAT IS ABOUT ONLINE LEARNING? - Fauji Sri Astuti; Zulfan Saam; M. Adi Jaya Adi Putra (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2022)
This article is entitled What's About Online learning? This article aims to describe what online learning is and at the same time describe how online learning is implemented in a school and the constraints and solutions that are given to the various challenges faced in learning. The study also found three sub-focuses, they are (1) the implementation of online learning policies, (2) the obstacles faced by teachers, parents, and students in online learning, and (3) solutions that were given to obstacles in online learning. In addition, the researchers also found its benefits in online learning experienced by parents, students, and teachers. Data collection techniques used were observation, interviews, and documentation. Data analysis techniques used were data reduction, data display, and conclusion. The informants consisted of principals, school supervisors, 12 students, 12 parents, and school committee administrators. The results indicated that the implementation of online learning policies has not gone well. Its success was inseparable from the discipline of all participants, they are schools, teachers, parents, and students. Therefore, from the school, it was required a systematic structure and simple schedule that could make it easier for parents to supervise children's learning. The involvement of parents influences the successful learning for children themselves, because education for children was not completely left to the school. The solutions given to the existing constraints are not appropriate and need to be re-examined.